1999
DOI: 10.2486/indhealth.37.415
|View full text |Cite
|
Sign up to set email alerts
|

A Four-Year Follow-Up Study on Subjective Symptoms and Functional Capacities in Workers Using Hand-Held Grinders.

Abstract: Abstract:Fifty-three grinders in the metal industry were re-examined 4 years after their first examination. Information about age, occupation, daily vibration exposure, drinking and smoking habits, and presence of subjective symptoms such as vibration-induced white finger (VWF), and numbness and pain in the fingers was collected during the first and second examination. Cold provocation test (10°C110 min) was also employed to evaluate disturbances in the peripheral circulatory and peripheral nerves in all subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…It has been suggested that musculoskeletal pain induced by exposure to vibrating devices used in various occupations, may have a vascular component (Ogasawara et al, 1997; Dowd et al, 1998; Mirbod et al, 1999). We have previously demonstrated that exposure to vibration produces chronic muscle pain (Chen et al, 2010; Dina et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that musculoskeletal pain induced by exposure to vibrating devices used in various occupations, may have a vascular component (Ogasawara et al, 1997; Dowd et al, 1998; Mirbod et al, 1999). We have previously demonstrated that exposure to vibration produces chronic muscle pain (Chen et al, 2010; Dina et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…In other studies reduced strength has been reported among people who use hand-held vibrating tools in their daily work. A 7% reduction in grip strength has been reported among grinders in a four year follow up study (17) and loss of 21% in grip strength in the hand during a two year follow up study of lumberjacks with Raynaud's phenomenon (8). We have recently reported reductions in grip and pinch strength of 7% and 9%, respectively, in full-time workers making rock crushing equipment compared with controls.…”
Section: Discussionmentioning
confidence: 92%
“…A significant decrease in hand grip strength was detected in metal industrial workers who used hand-held grinders, in a 4-year follow-up study, indicating that prolonged occupational exposure should be considered as a risk for work-related MSDs [19]. The existence of musculoskeletal symptoms amongst individuals who stand for prolonged periods is well recognized [6,20,21,22] as is the existence of these symptoms amongst individuals who sit for prolonged periods [6,23,24,25].…”
Section: Resultsmentioning
confidence: 98%